(untitled) (Functional Plant Breeding Journal, 2022)
The use of active teaching methodologies puts the student as the protagonist of their learning process and the teacher as a facilitator of their development: a tutor. In the context of Histology, the use of practical multitasking activities is a form of active learning. This study aims to report the student teacher experience in the use of active methodologies as a teaching-learning strategy of Histology in a higher education institution. The study of Histology, which is part of the studies of Integrated Organic Systems, presents itself with practices associated with the study goals of Small Group Learning (SGL), so that students previously instruct the subject to be explored. The dynamics consists of activities carried out in the Histology Laboratory under the guidance of the tutor. The activities in the laboratories are fortresses in stations, which have a script with specific commands. It was observed that the guided practical activities lead the students to make conclusions on their own, since they are inviting and challenging. This makes the process of learning Histology more effective because the practice creates the connection with the theoretical content, which is useful for its understanding. Thus, it is clear that there is a greater use of methodologies in the teaching-learning process of Histology, through learning gains and the development of autonomy.